1994
DOI: 10.1111/j.1752-0606.1994.tb01007.x
|View full text |Cite
|
Sign up to set email alerts
|

How Personal Can Training Get?

Abstract: Training on the person of the therapist calls for trainees to deal with their personal issues in relation to the therapy they do. Growing controversy about dual relationships has the field wondering where to draw the line between training and therapy. This paper offers a distinction between dual qualities and dual relationships to clarify the issue. An illustration of clinical training with qualities of therapy demonstrates an effort to maintain proper boundaries in training on the person of the therapist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 3 publications
1
67
0
1
Order By: Relevance
“…Guy and Brown found this to be an emotional benefit to practicing psychotherapy. Aponte (1994) referred to the impact on personal growth as "selfunderstanding," which my participants also labeled as "self-awareness." Sawatsky, Jevne, and Clark (1994) originated the concept of "Becoming Empowered" as a process of effectiveness development.…”
Section: Links To Previous Researchmentioning
confidence: 98%
See 2 more Smart Citations
“…Guy and Brown found this to be an emotional benefit to practicing psychotherapy. Aponte (1994) referred to the impact on personal growth as "selfunderstanding," which my participants also labeled as "self-awareness." Sawatsky, Jevne, and Clark (1994) originated the concept of "Becoming Empowered" as a process of effectiveness development.…”
Section: Links To Previous Researchmentioning
confidence: 98%
“…Furthermore, this study has important implications for training, as well. Aponte (1994) interviewed a trainee about how her professional experience impacted her personal life. Aponte concluded that the person of the therapist training "gave a trainee the opportunity to further personal growth through a clinical experience while helping her professional performance" (p. 15).…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…(Terapeuta 1 Bogotá, 2016) La narrativa no es solo escribir; es que con ese escrito, y con la anuencia, el permiso de los consultantes, ir leyendo, ir resignificando a tiempo presente, lo que está ahí, escrito, lo que está ahí narrado que muchas veces se narra con dolor, con resentimiento, con tristeza, cuando la persona lo escucha, cuando la persona lo habla, lo elabora, lo llora, lo ríe, sale con un significado distinto de esa vivencia. (Terapeuta 1 Barranquilla, 2016) Otra perspectiva referenciada por su utilidad en la intervención terapéu-tica es la propuesta por Aponte (1994) sobre la dimensión espiritual de la terapia. Esta integra elementos del enfoque estructural con la perspectiva narrativa y colaborativa, a través de los cuales apunta a la intervención del daño causado por la violencia en el espíritu de las personas.…”
Section: Razones Para Otorgar Un Lugar Específico a La Intervención Tunclassified
“…Self of the therapist work is based on the notion that, if left unexplored, therapists' personal life experiences and family histories will become a barrier in their work with clients (Aponte, 1994). Specifically, self of the therapist work has involved assisting students in exploring the patterns that exist within in their own families of origin in an effort to be less reactive to transgenerational patterns, and in order to create greater objectivity on the part of the therapist (Aponte et al, 2009;Aponte & Winter, 1987;Guerin & Hubbard, 1987).…”
mentioning
confidence: 99%